2020
DOI: 10.33192/smj.2020.03
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Enhanced Recovery after Surgery (ERAS) Protocols for Elderly Colorectal Cancer Patients

Abstract: Objective: Enhanced recovery after surgery (ERAS) provides a multimodal approach to postsurgical recovery, seeking to reduce a patient's stress response and promoting recovery. This study aimed to determine the suitability of ERAS protocols for elderly patients above 75 years of age. Methods: This is a retrospective analysis of all patients who had undergone major colorectal resections under ERAS protocols in Khoo Teck Puat Hospital, Singapore and Faculty of Medicine Siriraj Hospital, Thailand between 2013 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In 2020, Papaconstantinou et al found that Amyand's hernia which is a very rare kind of inguinal hernia complicated to a case of appendicitis. He stated that this type of hernia reconstructed by tailoring each case individually according to extension of the inflamed inguinal canal [29].…”
Section: Published Researches In the 21 Th Centurymentioning
confidence: 99%
“…In 2020, Papaconstantinou et al found that Amyand's hernia which is a very rare kind of inguinal hernia complicated to a case of appendicitis. He stated that this type of hernia reconstructed by tailoring each case individually according to extension of the inflamed inguinal canal [29].…”
Section: Published Researches In the 21 Th Centurymentioning
confidence: 99%